Restricted nasal-only breathing during self-selected low intensity training does not affect training intensity distribution - Rappelt, Ludwig; Held, Steffen; Wiedenmann, Tim; Deutsch, Jan-Philip; Hochstrate, Jonas; Wicker, Pamela; Donath, Lars (Frontiers in Physiology, 2023)
Low-intensity endurance training is frequently performed at gradually higher training intensities than intended, resulting in a shift towards threshold training. By restricting oral breathing and only allowing for nasal breathing this shift might be reduced. Nineteen physically healthy adults (3 females, age: 26.5 ± 5.1 years; height: 1.77 ± 0.08 m; body mass: 77.3 ± 11.4 kg; V̇O2peak: 53.4 ± 6.6 ml·kg−1·min−1) performed 60 min of self-selected, similar (144.7 ± 56.3 vs. 147.0 ± 54.2 W, p = 0.60) low-intensity cycling with breathing restriction (nasal-only breathing) and without restrictions (oro-nasal breathing). During these sessions heart rate, respiratory gas exchange data and power output data were recorded continuously. Total ventilation (p < 0.001, ηp2 = 0.45), carbon dioxide release (p = 0.02, ηp2 = 0.28), oxygen uptake (p = 0.03, ηp2 = 0.23), and breathing frequency (p = 0.01, ηp2 = 0.35) were lower during nasal-only breathing. Furthermore, lower capillary blood lactate concentrations were found towards the end of the training session during nasal-only breathing (p = 0.02, ηp2 = 0.17). Even though discomfort was rated marginally higher during nasal-only breathing (p = 0.03, ηp2 = 0.24), ratings of perceived effort did not differ between the two conditions (p = 0.75, ηp2 = 0.01). No significant “condition” differences were found for intensity distribution (time spent in training zone quantified by power output and heart rate) (p ≥ 0.24, ηp2 ≤ 0.07). Nasal-only breathing seems to be associated with possible physiological changes that may help to maintain physical health in endurance athletes during low intensity endurance training. However, it did not prevent participants from performing low-intensity training at higher intensities than intended. Longitudinal studies are warranted to evaluate longitudinal responses of changes in breathing patterns.